The relationship between regular martial arts practice (judo and wrestling) and neurocognitive variables in children and adolescents: a scoping review - Sevilla-Sanchez, Marta; Dopico Calvo, Xurxo; Morales, Jose; Carballeira, Eduardo (Revista de Artes Marciales Asiáticas, 2025)
This scoping review aims to map existing evidence on the effects of judo and wrestling on cognitive performance in youth. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) was followed, retrieving documents from inception up to March 2025. The search encompassed six electronic databases: Web of Science, SCOPUS, PubMed, Sport Discus, ERIC, and PsycInfo; and other identification methods. Eligible studies included original studies involving judo or Olympic wrestling practices, with or without control groups, acute or chronic, of both sexes, age >6 and <18 years old, from any competitive level. Quantitative assessments of executive functions, cognitive performance, or academic achievement were required for inclusion. A total of 1368 studies were initially identified, and after applying inclusion and exclusion criteria, 10 articles were included in this scoping review, encompassing a combined sample of 683 participants (50% males). As a result, despite the heterogeneous nature of interventions with varying types and characteristics, the studies consistently revealed a positive association between judo or wrestling practice and behavioral and neurocognitive variables. Notwithstanding, it is essential to note that the suboptimal overall quality of the included studies. The findings suggest potential executive function benefits from judo or wrestling in youth. However, results require cautious interpretation due to limited rigorous research. Future studies should examine dose-response relationships considering age, maturation, experience, and include active control groups.